Perencanaan Produksi Batch pada Industri Makanan untuk Meningkatkan Produktivitas - Vaniloran Elysa Andriani; Nur Afni; Nur Indrianti (Jurnal Optimalisasi, 2022)
The batch production system is one of the strategies used by the industry to meet increasingly varied consumer demands. More product variations can result in an increase in the total setup time as a result of the many production processes switching from different families. This study aims to plan batch production at Bakpia Pathok Vista (UBV) SMEs to increase productivity by reducing setup and idle time. Production planning includes job sequencing and operator allocation. A heuristic algorithm was proposed to solve the problem. The results showed that production planning based on the proposed algorithm could reduce the total setup time and idle time by 15.63% and 92.67%, respectively, so that productivity increases by 31.67% from the previous condition. This research can be further developed by considering operator overtime and minimizing makespan.